Data benchmarking through a longitudinal study in high-level men`s volleyball - Drikos, S.; Tsoukos, A. (International Journal of Performance Analysis in Sport, 2018)
A benchmark is a reference point for comparisons established from the value of a performance indicator. In order to create benchmarks for volleyball, we used performance data from each team of the Greek Volley League from the season 2005-2006 until the season 2016-2017 (N = 143). We considered the effectiveness of 14 parameters from five skills: serve, attack after passing, attack after defence, block and pass. The results showed that high-level teams of the Greek championship, which finished in positions 1-4, had as benchmarks: (a) in serve, two aces every five serve errors, while teams 9-12 had two aces every six errors, (b) in attack after passing one error or one passive block every four kills, while teams 9-12 had one every five kills, (c) in attack after defence one error or one passive block every three kills versus every two kills for 9-12 and (d) one error every nine passes on the target against every seven passes for 9-12. Overall, the results of this study indicate that success in volleyball can be explained with skill performance indicators, expressed as the ratio of successful to unsuccessful attempts, or with a ratio of successful attempts per set, in case of block skill.